Engajamento Popular de Base: uma abordagem geográfica-histórica da criação e desenvolvimento do Jardim Nova Pilar em Pilar do Sul (SP) - Santos, Simone Fabiano dos (Universidade Federal de São Carlos, 2025)
Understanding history is fundamental to living the present well and planning the future. This work investigates the context of the creation of the Jardim Nova Pilar Neighborhood from a geographical-historical perspective, analyzing the social movements that influenced society in the 1980s. Using a qualitative and bibliographic methodology, it analyzes historical and documentary records to understand the development process of the neighborhood. The collection of photographs and oral reports are also part of this research. To understand the territory, lived and built, a Miltonic approach was used. The central question focuses on social movements that encouraged residents to seek decent housing conditions. How these actions changed the space, previously a wasteland, now a territory full of meanings.
Grassroots Popular Engagement: a geographical-historical approach to the creation and development of Jardim Nova Pilar in Pilar do Sul (SP)
Keywords: Geografia histórica; Movimentos sociais; Território; Historical geography; Social movements; Territory; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA